Green Entrepreneurial Intention and Entrepreneurship Education: A Literature Review Study - Rahmanto, Andi Adam; Siswandari, Siswandari; Sangka, Khresna Bayu (Economic Education and Entrepreneurship Journal, 2024)
This study aims to explore the development and impact of entrepreneurship education on green entrepreneurial intentions, based on a descriptive analysis of 46 articles published between 2013 and 2023. The method used in this research is Systematic Literature Reviews. The analysis showed a significant growth in publications related to the topic of green entrepreneurial intention, with the highest peak of publications occurring in 2023. Entrepreneurship education has been identified as a key factor influencing green entrepreneurial intentions, with previous studies showing the positive impact of this education on green entrepreneurial intentions through strengthening the desire to start a business and instilling sustainability values. Studies have also shown that entrepreneurship education can influence green entrepreneurial intentions by shaping positive attitudes and self-efficacy, and developing sustainability-related knowledge and skills. Support from educational institutions and government act as moderators that strengthen the relationship between green entrepreneurial intention and behavior. Overall, green entrepreneurship education is an important element in developing environmentally conscious entrepreneurs, with a significant impact on young people's intention to start a green business.Keywords: Entrepreneurial Education, Green entrepreneurial Intention, EnvironmentDOI: http://dx.doi.org/10.23960/E3J/v7i1.103-108